2017
DOI: 10.17957/ijab/15.0232
|View full text |Cite
|
Sign up to set email alerts
|

High Grain Diet Triggers Inflammation in the Goat Uterus: A Comprehensive Regulation Diet Modulates the Immune Response

Abstract: The aim of the present study was to explore the causal association between the increase in circulating subacute ruminal acidosis (SARA)-induced lipopolysaccharide (LPS) levels and uterine inflammation; moreover this study sought to evaluate the role of a comprehensive regulation diet in combating the inflammatory effects of a high grain diet. Twelve dairy goats were randomly assigned to two groups. One group was provided a high-concentrate buffered diet as the comprehensive regulation group (RG) control while,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Importantly, increased peripheral blood LPS levels could be observed when the endotoxin inflow into the liver exceeds the hepatic detoxification capacity [ 12 , 17 ]. In addition, it has been reported that a high-concentrate diet-triggered increase in ruminal LPS concentration induces inflammatory gene expression in the uterus of cows [ 5 ] and goats [ 6 ]. The uterine inflammation-induced intrauterine LPS production was also reported to accumulate in the follicular fluid [ 14 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, increased peripheral blood LPS levels could be observed when the endotoxin inflow into the liver exceeds the hepatic detoxification capacity [ 12 , 17 ]. In addition, it has been reported that a high-concentrate diet-triggered increase in ruminal LPS concentration induces inflammatory gene expression in the uterus of cows [ 5 ] and goats [ 6 ]. The uterine inflammation-induced intrauterine LPS production was also reported to accumulate in the follicular fluid [ 14 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium butyrate (NaB) is used as an anti-inflammatory agent to prevent SARA (Bilal et al, 2017). NaB supplement administration evokes the reduction of LPS and pro-inflammatory cytokine concentrations (Aabdin et al, 2018).…”
Section: B) Sodium Butyrate (Nab)mentioning
confidence: 99%
“…LF associates with protein content and milk acidity (Guo et al, 2010) and single nucleotide polymorphisms (SNP) could be used for marker assisted selection on mastitis susceptibility (Ateya et al, 2016). Toll-like receptor 4 (TLR4) is located on the cell surface and initiates innate immune responses (Bilal et al, 2017). TLR4 gene is located at chromosome 8 (NC_030815.1) in goats.…”
Section: Introductionmentioning
confidence: 99%